Top Management Team Functional Background Diversity and Firm Performance: Examining The Roles of Team Member Colocation and Environmental Uncertainty - Cannella, Albert A.; Park, Jong-Hun; Lee, Ho-Uk (Academy of Management Journal, 2008)
Prior findings on the association between top management team (TMT) functional diversity and firm performance have been inconsistent. We consider the moderating effects of internal context (colocation of TMT members) and external context (environmental uncertainty) on the TMT diversity-firm performance relationship. Additionally, we consider both dominant and intrapersonal functional diversity. In our results from 207 U.S. firms in 11 industries, the effects of TMT functional diversity on firm performance become more positive as the proportion of TMT members with offices in the same location increases. The effects of intrapersonal functional diversity also become more positive as environmental uncertainty increases.